Personal Financial Behavior in Surakarta Students - Ari Susanti; Septiana Widiastuti (International Journal of Entrepreneurship, Business, and Creative Economy, 2021)
Personal financial literacy among students is still minimal attention. This study aims to examine financial literacy, financial attitude, and lifestyle towards student financial behavior. Students who became respondents were 730 populations and 88 samples. Respondents are STIE Surakarta students who study at night and, on average, have worked. The analysis used is multiple linear analysis with the SPSS version 21 analysis tool. This study indicates that financial literacy has no significant effect on financial behavior, while financial attitude and lifestyle variables significantly affect financial behavior.